Performance calculations of the X‐ray powder diffraction beamline at NSLS‐II. (8th February 2013) - Shi, Xianbo; Ghose, Sanjit; Dooryhee, Eric
Abstract : The X‐ray Powder Diffraction (XPD) beamline at the National Synchrotron Light Source II is a multi‐purpose high‐energy X‐ray diffraction beamline with high throughput and high resolution. The beamline uses a sagittally bent double‐Laue crystal monochromator to provide X‐rays over a large energy range (30–70 keV). In this paper the optical design and the calculated performance of the XPD beamline are presented. The damping wiggler source is simulated by the SRW code and a filter system is designed to optimize the photon flux as well as to reduce the heat load on the first optics. The final beamline performance under two operation modes is simulated using the SHADOW program. For the first time a multi‐lamellar model is introduced and implemented in the ray tracing of the bent Laue crystal monochromator. The optimization and the optical properties of the vertical focusing mirror are also discussed. Finally, the instrumental resolution function of the XPD beamline is described in an analytical method.